THE USE OF MNEMONICS IN TEACHING PRIMARY SCHOOL CHILDREN THEIR NATIVE LANGUAGE AND READING LITERACY (Academia Science Repository, 2023)
This article gives reviews and recommendations about the benefits of mnemonics, which is very relevant in the educational process today, about classes for the development of brain activity of younger schoolchildren, as well as about very convenient methods used in teaching 1st grade students their native language and reading literacy.